A systematic review of micro correlates of maternal mortality - Mohamed Nor, Norashidah (Walter de Gruyter GmbH, 2018)
In the year 2000, the World Health Organization launched the Millennium Development Goals (MDGs) which were to be achieved in 2015. Though most of the goals were not achieved, a follow-up post 2015 development agenda, the Sustainable Development Goals (SDGs) was launched in 2015, which are to be achieved by 2030. Maternal mortality reduction is a focal goal in both the MDGs and SDGs. Achieving the maternal mortality target in the SDGs requires multiple approaches, particularly in developing countries with high maternal mortality. Low-income developing countries rely to a great extent on macro determinants such as public health expenditure, which are spent mostly on curative health and health facilities, to improve population health. To complement the macro determinants, this study employs the systematic review technique to reveal significant micro correlates of maternal mortality. The study searched MEDLINE, PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Science Direct, and Global Index Medicus of the World Health Organization. Our search was time framed from the 1st January, 2000 to the 30th September, 2016. In the overall search result, 6758 articles were identified, out of which 33 were found to be eligible for the review. The outcome of the systematic search for relevant literature revealed a concentration of literature on the micro factors and maternal mortality in developing countries. This shows that maternal mortality and micro factors are a major issue in developing countries. The studies reviewed support the significant relationship between the micro factors and maternal mortality. This study therefore suggests that more effort should be channelled to improving the micro factors in developing countries to pave the way for the timely achievement of the SDGs' maternal mortality ratio (MMR) target.